The roles of prior experience and the location on the severity of supply chain disruptions. Issue 16 (18th August 2022) - Baghersad, Milad; Zobel, Christopher W.; Lowry, Paul Benjamin; Chatterjee, Sutirtha
Abstract : This study examines relationships between the location of supply chain disruptions (SCDs) within the supply chain, a firm's experience with SCDs, and the disruption severity. Using organisational learning theory, we propose that an organisation's prior experience with SCDs will reduce the negative influence of future disruptions. However, the location of disruption occurrence (internal to the firm vs. external to the firm) also plays a vital role in the severity of future disruptions. We consider two measures of SCD severity to quantify the extent of negative influence on firms: (1) the initial loss of return on assets (ROA) and (2) the total loss of ROA over time. We empirically evaluate the performance of 262 publicly traded U.S. firms that experienced an SCD. Our study shows that the influence of internal and external SCDs on firms can be different when firms do and do not have experience with similar events. More specifically, the results show that when firms have not experienced a similar event in the past, internal SCDs are associated with a higher disruption severity than are external SCDs. The results also show that prior experience significantly decreases the disruption severity suffered by firms after internal SCDs.